Effect of Hot Glue Additive on the Rheological Properties of Asphalt Cement and Mixtures Performance - Ahmed, Sheelan A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2023)
In general, the physical and rheological properties of asphalt binder are directly affecting the resistance of asphalt mix to the permanent deformation (rutting), water damage, and thermal cracking. The degradation in these properties leads to severe distresses that appear in the pavement and, consequently, make the repair and maintenance very expensive. Since the modified-asphalt cement may help to minimize such aforementioned distresses, this research is established for this purpose. It aims to investigate the physical and rheological properties of modified-asphalt cement with silicone, dense silicone rubber, and ethylene propylene diene monomer rubber. Five contents for each type of hot glue are investigated; 0.4, 0.8, 1.2, 1.6, and 2% of the asphalt cement weight. Conventional asphalt cement tests such as penetration, softening point, dynamic viscosity, and ductility tests are conducted to evaluate the hot glue-modified asphalt cement properties. Moreover, the Marshall and indirect tensile strength tests are conducted to examine the effect of hot glue on the performance of the asphalt mixtures at concentrations of 0.8 and 1.6% of the asphalt cement weight. The results show that the hot glue-modified asphalt cement leads to an increase in the hardness and consistency, and a reduction in the temperature susceptibility of asphalt cement. These features lead to better Marshall stability and tensile strength ratio, as compared with the standard asphalt cement mixture.